The Analysis of Primary School Teachers Ability in The Application of ICT-Based Learning Media In Tarogong Kidul District - Irfan Hilman; Suci Zakiah Dewi (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
The purpose of this research is to analyze the ability of elementary school teachers in the application of learning media based on Information and Communication Technology (ICT). The main objectives are the teacher's understanding of ICT-based learning media, the ability of teachers in designing ICT-based learning media, the ability of teachers in the use of ICT-based learning media, factors that can support and inhibit the application of ICT-based learning media, and how teachers overcome obstacles in the application of ict-based learning media. The research method used by the author is mixed methods research method or mixed research method that is, by combining between qualitative and quantitative research types. The subject of this study was a public elementary school teacher in tarogong kidul area. The sample of this study was as many as 30 teachers. Instruments used in the form of questionnaires, observations and interviews. Based on the results of the instrument test obtained teacher's understanding of learning media by 85.6%, the ability of teachers in designing ICT-based learning media by 85.6%, then the ability of teachers in the use of ICT-based learning media by 85.4%. The supporting factors in terms of teacher ability are the implementation of training in the use of ICT devices and designing ICT-based learning media. From the results obtained, it can be concluded that the ability of elementary school teachers in the application of ICT-based learning media in the Tarogong Kidul area is very good.